2020
DOI: 10.1159/000508938
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ciliary Dyskinesia: The Impact of Taste Receptor (<b><i>TAS2R38</i></b>) Gene Polymorphisms on Disease Outcome and Severity

Abstract: Background: Primary ciliary dyskinesia (PCD) is a rare genetic disease leading to recurrent respiratory infections of upper and lower airways. Chronic rhinosinusitis (CRS) and bronchiectasis are very common in PCD patients. Recently, it has been shown the presence of taste receptors in respiratory tract and the possible involvement of bitter taste receptor TAS2R38 gene in susceptibility to respiratory infections and rhinosinusitis. Objective: Aim of this study was to evaluate the frequency of TAS2R38 polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the study of 35 patients with PCD, the PAV/PAV diplotype was associated with less frequent respiratory exacerbations compared to patients with the PAV/AVI or AVI/AVI diplotypes 32 …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In the study of 35 patients with PCD, the PAV/PAV diplotype was associated with less frequent respiratory exacerbations compared to patients with the PAV/AVI or AVI/AVI diplotypes 32 …”
Section: Resultsmentioning
confidence: 93%
“…However, the supertaster haplotype (PAV/PAV) for TAS2R38 correlated with an improved QoL, showing significantly lower SNOT‐22 scores 29 . For patients with PCD, a genotypic study showed a lower percentage of supertasters (PAV/PAV) with frequent respiratory exacerbations compared with tasters (PAV/AVI) and nontasters (AVI/AVI) 32 . In addition, there were no P aeruginosa infections with the supertaster (PAV/PAV) haplotype.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, the frequency of the PAV allele (i.e., the functional allele) was significantly reduced in CF patients with nasal polyps that required additional sinus surgery, and in CF patients that were colonized with P. auruginosa [ 70 ]. Finally, TAS2R38 polymorphisms have also been described in patients with primary ciliary dyskinesia [ 71 ] and sweet taste receptors have been implicated in acute respiratory stress syndrome [ 45 ]. These studies demonstrate that taste receptors might contribute to physiological and pathological phenotypes and that genetic variations in these receptors might contribute to disease severity and risk.…”
Section: Bitter and Sweet Taste Receptors In The Respiratory Tractmentioning
confidence: 99%